And Life Is Changed Forever: Holocaust Childhoods Remembered - Glassner, Martin Ira; Krell, Robert; Holocaust Child Survivors of Connecticut (Landscapes of childhood, 2006)
Contains brief memoirs, some of which describe experiences in the Holocaust. Includes commentary by psychologist and child survivor Robert Krell. Partial contents:
Keywords: Biography; Holocaust, Jewish (1939-1945); Connecticut; History and criticism; Influence; Holocaust, Jewish (1939-1945); Jewish children in the Holocaust; Personal narratives; Personal narratives; Holocaust survivors; dept.egm; faculty_collection

Photojournal: Turkmenistan - Yacher, L. (Focus on Geography, 2006)
Keywords: Asia; Eurasia; Turkmenistan; West Asia; dept.egm; geographical research

Tres nuevas especies de jaltomata schlechtendal (solanaceae) del norte del perú - Gonzalez, Segundo Leiva; Mione, Thomas; Yacher, Leon (Arnaldoa, 2006)
Keywords: dept.egm; ⛔ No DOI found

Shopping to save: green consumerism and the struggle for northern Maine - Harrison, Blake (Cultural Geographies, 2006)
Between 2001 and 2003, Roxanne Quimby - then the sole owner of a natural personal-care products company named Burt's Bees - invested millions of dollars of her company's profits in tens of thousands of acres of forestland in northern Maine. Her intention was to donate that land to the United States government on behalf of a controversial national park proposed for the region - the Maine Woods National Park. Quimby's actions set off sharp debates between policy makers, environmentalists and residents of northern Maine. As this article suggests, those debates were informed in part by their association with green consumerism. When consumers purchase `environmentally friendly' products like those made by Burt's Bees, they typically envision their actions as having positive consequences for places associated directly with the production and consumption of that product. In this case, however, profits from a green consumer product were reinvested outside its immediate commodity chain, thereby implicating green-consumer decisions in a politics of identity and landscape control beyond that product's lifecycle. This paper explores that process, suggesting that even the most well-intended consumer choices can carry social and environmental consequences into new and perhaps unexpected terrain. When we shop to save, we can never be quite certain of what it is that we are saving.
Keywords: Apoidea; Maine; North America; United States; consumption behavior; dept.egm; profitability